Simulation study of the impacts of E-region density on the growth of equatorial plasma bubbles - Yokoyama, Tatsuhiro (Frontiers in Astronomy and Space Sciences, 2024)
Equatorial plasma bubbles (EPBs) in the ionospheric F region are notorious for causing severe scintillation in radio signals, posing significant challenges for communication and navigation systems. Understanding and forecasting EPB occurrence is crucial from a space weather perspective, given their impact on satellite and terrestrial communication. In this study, we present the impacts of E-region conductivity on the generation of EPBs by using the 3D high-resolution bubble (HIRB) model. By changing the production rate of NO+ ions in the E region, the flux-tube-integrated linear growth rate of the Rayleigh–Taylor instability can be modified. Multiple simulation runs show that even a moderate variation of the growth rate turns into a significant difference in EPB growth into the top of the ionosphere. This is a major factor that has made forecasting EPB generation quite difficult for several decades.